2013
DOI: 10.1242/jcs.123364
|View full text |Cite
|
Sign up to set email alerts
|

The Toxoplasma gondii centrosome is the platform for internal daughter budding as revealed by a Nek1 kinase mutant

Abstract: SummaryThe pathology and severity of toxoplasmosis results from the rapid replication cycle of the apicomplexan parasite Toxoplasma gondii. The tachyzoites divide asexually through endodyogeny, wherein two daughter cells bud inside the mother cell. Before mitosis is completed, the daughter buds form around the duplicated centrosomes and subsequently elongate to serve as the scaffold for organellogenesis and organelle partitioning. The molecular control mechanism of this process is poorly understood. Here, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 63 publications
11
101
0
Order By: Relevance
“…1B). Binding of anti-centrin antibodies to centrosomes shows that oocyst walls are permeabilized (23). Transient expression of GAP40-YFP, which highlights the inner membrane complex (24), shows that AAL binds to T. gondii nuclei throughout the tachyzoite cell cycle (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1B). Binding of anti-centrin antibodies to centrosomes shows that oocyst walls are permeabilized (23). Transient expression of GAP40-YFP, which highlights the inner membrane complex (24), shows that AAL binds to T. gondii nuclei throughout the tachyzoite cell cycle (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…This haploid parasite replicates asexually by the simplest replication mode, termed endodyogeny, where the budding cycle (cytokinesis) is tied to only a single nuclear cycle (S/M) generating two cells per cycle. It is known that the centrosome serves as a central hub by nucleating spindle microtubule and scaffolding the components of daughter cells [3]. However, the mechanistic coordination of these two events remains largely unclear.…”
mentioning
confidence: 99%
“…With a TgMAPK-L1 deficient parasite line, it was shown that TgMAPK-L1 limits centrosome core duplication to only once per cell cycle, and promotes the connection of the nuclear centrocone and the daughter basal complex [4]. Furthermore, a previously reported kinase, TgNek1-2, that plays a role in centrosome splitting, showed similar localization pattern to TgMAPK-L1 but resides towards the centrosome [3]. In the absence of TgNek1-2 activity, the centrosome duplicates but remains clustered, resulting in formation of a single daughter bud and failure of mitosis [3].…”
mentioning
confidence: 99%
“…Toxoplasma SAS-6 is found at the centrioles during tachyzoite replication (87). Nek1 is recruited to tachyzoite centrioles prior to duplication and is essential to their subsequent separation (100). Toxoplasma expresses three centrin isoforms: all localize to centrioles, and centrin 2 and centrin 3 are found at additional subcellular sites (95,103,104).…”
Section: Microtubule-associated Proteinsmentioning
confidence: 99%
“…SFA2 and SFA3 filaments connect centrioles to emergent daughters; conditional depletion of either protein blocks bud formation (88). A temperature-sensitive Nek1 mutation demonstrates that centriole separation is vital to nuclear division and counting daughters (100,124). Loss of Nek1 activity prevents completion of mitosis at the restrictive temperature.…”
Section: Microtubule-dependent Processesmentioning
confidence: 99%